Taxonomic revision of the genus Spiranthes (Orchidaceae) in Taiwan - Suetsugu, Kenji; Hsu, Tian-Chuan (Phytotaxa, 2023)
The taxonomy of Spiranthes is highly challenging due to its phenotypic plasticity, morphological convergence, and hybridization. This paper presents a re-evaluation of the genus Spiranthes (Orchidaceae) in Taiwan, with special reference to the taxonomic identity of S. suishaensis that has often been considered the earlier name of S. nivea or S. hongkongensis. Nonetheless, the floral dissection of the type specimen revealed that S. suishaensis has a well-developed rostellum that separates the stigma and pollinarium of each flower, in contrast to autogamous taxa such as S. nivea and S. hongkongensis. Given the morphological evidence and that only S. sinensis was collected in the S. suishaensis type locality, we concluded that S. suishaensis is neither an earlier name for S. nivea nor S. hongkongensis but a synonym of S. sinensis. During morphological comparisons of S. suishaensis with other taxa of S. sinensis complex, we also found that the taxon illegitimately described as “S. minutiflora” could be treated as a variant of S. nivea. Given that it is distinguishable from S. nivea var. nivea by its more densely pubescent rachis and ovaries (vs. sparsely pubescent rachis and ovaries), narrower sepals with white tinged with pink or purple at apex (vs. wider and entirely white sepals), and papillose labellum disc (vs. almost glabrous labellum disc), we described it as a new variety of S. nivea, which we propose to name S. nivea var. papillata T.C. Hsu & Suetsugu. Consequently, we concluded that three species (S. sinensis, S. hongkongensis, and S. nivea [including var. nivea and var. papillata]) and one hybrid, S. australis × S. sinensis, occur in Taiwan.